Welcome to Westonci.ca, the ultimate question and answer platform. Get expert answers to your questions quickly and accurately. Discover solutions to your questions from experienced professionals across multiple fields on our comprehensive Q&A platform. Connect with a community of professionals ready to help you find accurate solutions to your questions quickly and efficiently.
Sagot :
To find the coefficient of the \(x^7 y^3\) term in the expansion of \((x-2y)^{10}\), we can use the binomial theorem. The binomial theorem states that:
[tex]\[ (a + b)^n = \sum_{k=0}^{n} \binom{n}{k} a^{n-k} b^k \][/tex]
In this problem, we have \(a = x\), \(b = -2y\), and \(n = 10\). We are interested in the term where the power of \(y\) is 3, which corresponds to \(k = 3\).
The general term in the expansion is given by:
[tex]\[ \binom{n}{k} x^{n-k} (-2y)^k \][/tex]
Substituting \(n = 10\), \(k = 3\), and \(n-k = 7\), we have:
[tex]\[ \binom{10}{3} x^{7} (-2y)^3 \][/tex]
Now we need to calculate each component of this term:
1. Calculate the binomial coefficient \(\binom{10}{3}\):
[tex]\[ \binom{10}{3} = \frac{10!}{3! (10-3)!} = \frac{10!}{3! 7!} = \frac{10 \times 9 \times 8}{3 \times 2 \times 1} = 120 \][/tex]
2. Determine the powers of \(x\) and \(y\):
Since we are dealing with \(k = 3\),
- The power of \(x\) is \(10 - 3 = 7\).
- The power of \(y\) is \(3\).
3. Calculate the coefficient for \((-2y)^3\):
[tex]\[ (-2y)^3 = (-2)^3 y^3 = -8 y^3 \][/tex]
4. Multiply the binomial coefficient by the coefficient of \((-2y)^3\):
[tex]\[ 120 \times (-8) = -960 \][/tex]
Thus, the coefficient of the \(x^7 y^3\) term in the expansion of \((x-2y)^{10}\) is \(-960\).
So, the correct answer is:
[tex]\[ \boxed{-960} \][/tex]
[tex]\[ (a + b)^n = \sum_{k=0}^{n} \binom{n}{k} a^{n-k} b^k \][/tex]
In this problem, we have \(a = x\), \(b = -2y\), and \(n = 10\). We are interested in the term where the power of \(y\) is 3, which corresponds to \(k = 3\).
The general term in the expansion is given by:
[tex]\[ \binom{n}{k} x^{n-k} (-2y)^k \][/tex]
Substituting \(n = 10\), \(k = 3\), and \(n-k = 7\), we have:
[tex]\[ \binom{10}{3} x^{7} (-2y)^3 \][/tex]
Now we need to calculate each component of this term:
1. Calculate the binomial coefficient \(\binom{10}{3}\):
[tex]\[ \binom{10}{3} = \frac{10!}{3! (10-3)!} = \frac{10!}{3! 7!} = \frac{10 \times 9 \times 8}{3 \times 2 \times 1} = 120 \][/tex]
2. Determine the powers of \(x\) and \(y\):
Since we are dealing with \(k = 3\),
- The power of \(x\) is \(10 - 3 = 7\).
- The power of \(y\) is \(3\).
3. Calculate the coefficient for \((-2y)^3\):
[tex]\[ (-2y)^3 = (-2)^3 y^3 = -8 y^3 \][/tex]
4. Multiply the binomial coefficient by the coefficient of \((-2y)^3\):
[tex]\[ 120 \times (-8) = -960 \][/tex]
Thus, the coefficient of the \(x^7 y^3\) term in the expansion of \((x-2y)^{10}\) is \(-960\).
So, the correct answer is:
[tex]\[ \boxed{-960} \][/tex]
Your visit means a lot to us. Don't hesitate to return for more reliable answers to any questions you may have. We hope you found what you were looking for. Feel free to revisit us for more answers and updated information. Get the answers you need at Westonci.ca. Stay informed by returning for our latest expert advice.